Nonsmooth optimization control based on a sandwich model with hysteresis for piezo-positioning systems - Yang, Sen; Tan, Yonghong; Dong, Ruili; Tan, Qingyuan (Zielona Góra: Uniwersytet Zielonogórski)
A nonsmooth optimization control (NOC) based on a sandwich model with hysteresis is proposed to control a micropositioning system (MPS) with a piezoelectric actuator (PEA). In this control scheme, the hysteresis phenomenon inherent in the PEA is described by a Duhem submodel embedded between two linear dynamic submodels that describe the behavior of the drive amplifier and the flexible hinge with load, respectively, thus constituting a sandwich model with hysteresis.
Keywords: optimization control; hysteresis; compensation; piezoelectric actuator; sandwich systems